PENGARUH LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY(CSR) TERHADAP HUBUNGAN UNEXPECTEDEARNINGS DANRETURNSAHAM - Amalia Ilmiani (Neraca, 2012)
The value relevance of earnings information will be even greater when there is uncertainty about companies’future prospect. This research uses corporate social responsibility (CSR) disclosure in annual report proxied uncertainty about companies’future prospect. The purpose of this research is to analyze the effect of CSR disclosure of both unexpected earnings and stock returns.The population of this research is a manufacturing company that is listed on Indonesian stock exchange in 2008-2010. Sampling method using a purposive sampling with the number of samples that meet the criteria are 123 companies. This research uses multiple regression analysis. The result of analysis hypothesis show that CSR disclosure have negative effects of correlation unexpected earnings and stock returns. CSR disclosure proved able to reduce uncertainty about companies’future prospect.